Kesempurnaan Suluk Dan Adab Para Murid - Valentina Adinda Febriani (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2021)
Here I will discuss about the perfection of mysticism and etiquette of the students. The first thing I will discuss is about Suluk, then in the Suluk chapter I will explain about the meaning of Suluk, the types and then the obligations of students in carrying out the exercises. Then I will explain about